2019
DOI: 10.1186/s13059-019-1878-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of commonly used analysis strategies for epigenome- and transcriptome-wide association studies through replication of large-scale population studies

Abstract: BackgroundA large number of analysis strategies are available for DNA methylation (DNAm) array and RNA-seq datasets, but it is unclear which strategies are best to use. We compare commonly used strategies and report how they influence results in large cohort studies.ResultsWe tested the associations of DNAm and RNA expression with age, BMI, and smoking in four different cohorts (n = ~ 2900). By comparing strategies against the base model on the number and percentage of replicated CpGs for DNAm analyses or gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 50 publications
2
31
0
Order By: Relevance
“…The relevance of confounding by leukocyte composition on the association between exposures and peripheral blood DNA methylation has been of interest (Heiss and Brenner 2017;van Rooij et al 2019). In post hoc analyses, we demonstrated the general weakening of top CpGs (with some signals not attaining nominal significance) when leukocyte composition was not considered.…”
Section: Discussionmentioning
confidence: 82%
“…The relevance of confounding by leukocyte composition on the association between exposures and peripheral blood DNA methylation has been of interest (Heiss and Brenner 2017;van Rooij et al 2019). In post hoc analyses, we demonstrated the general weakening of top CpGs (with some signals not attaining nominal significance) when leukocyte composition was not considered.…”
Section: Discussionmentioning
confidence: 82%
“…We used methylation M-values as their distribution is usually closer to Gaussian than methylation beta-values [ 54 ]. As a sensitivity analysis, we performed a more direct normalization of beta-values using rank-based inverse normal transformation (RINT) which was applied previously in the context of DNA methylation analyses and provides a Gaussian methylation distribution, which is not the case for the M-values [ 55 , 56 ].…”
Section: Methodsmentioning
confidence: 99%
“…Recently, van Rooij et al (30) also performed a benchmarking study comparing analysis approaches for transcriptome-wide analysis of RNA-seq in population-based studies, including when using continuous phenotypes in association testing. While we used similar statistical methods to theirs, we took a different analytical approach.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we did not study their effect because it was beyond the scope of our investigation. van Rooij et al (30) in their benchmarking study focusing on replication across cohorts, compared a few approaches for adjusting for technical covariates, including estimating and adjusting for latent confounders (38). They concluded that inclusion of more technical adjusting covariates, including hidden confounders, increases the rate of replication between studies.…”
Section: Discussionmentioning
confidence: 99%